Which social determinants of health have the highest impact in community oncology to advance patient care equity and improve health outcomes? A scoping review - Kayleigh R. Majercak; Emily F. Gorman; Nicholas J. Robert; Barbara Palmer; Henry Asante Antwi; C. Daniel Mullins (Cancer Medicine)
Abstract Introduction To better understand the SDOH‐health equity landscape within a community oncology setting to answer the research question, “Which SDOH can have the highest impact in community oncology to advance patient care equity and improve health outcomes?” Methods Arksey and O'Malley's scoping review framework was used to identify evidence related to SDOH and health equity in community oncology. The study was guided by the “10‐Step Framework for Continuous Patient Engagement” and a Community Advisory Board to assure relevance to patients and community providers. Literature was retrieved from literary databases and oncology organizations' websites. Eligible studies included discussion of SDOH and health equity as outlined by the World Health Organization and Centers for Disease Control and Prevention, respectively, and involved community oncology/cancer care in outpatient settings. Studies were excluded if the SDOH‐health equity relationship was not discussed. Results The review resulted in 61 exploratory and 17 confirmatory “intervention” studies addressing the impact of SDOH on health equity in community oncology settings. The most frequently SDOH‐health equity pairs identified were the SDOH categories, social inclusion and non‐discrimination, income and social protection, and structural conflict, all paired with the health equity category, access to care/treatment. Confirmatory studies focused on income and social protection (SDOH) and access to care/treatment (health equity); the SDOH categories, social inclusion and non‐discrimination and health/general literacy–patient, paired with the health equity category, and adherence/compliance. Conclusions Literature highlights the SDOH and health equity relationship within the realm of oncology. Most studies on SDOH/health inequities in the community oncology setting are exploratory. There is the need to shift from documentation of cancer inequities to implementing solutions.